The Power of Play: Gamification in Digital Health for Sustainable Behavioral Change - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The convergence of digital health technologies and behavioral science has opened new avenues for promoting healthier lifestyles. Among the most compelling st...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Machine Learning; Wearable Technology